Phosphorus-containing dibenzonaphthanthrenes: electronic fine tuning of polycyclic aromatic hydrocarbons through organophosphorus chemistry - Ascherl, Johannes D. R.; Neiß, Christian; Vogel, Alexander; Graf, Jürgen; Rominger, Frank; Oeser, Thomas; Hampel, Frank; Görling, Andreas; Kivala, Milan (Chemistry - a European journal, 2020)
A concise synthetic route towards a new family of phosphorus-containing polycyclic aromatic hydrocarbons starting from the versatile acridophosphine has been established. The structural and optoelectronic properties of these compounds were efficiently modulated through derivatization of the phosphorus center. X-ray crystallographic analysis, UV/Vis spectroscopic, and electrochemical studies supported by DFT calculations identified the considerable potential of these scaffolds for the development of organophosphorus functional materials with tailored properties upon further functionalization.